Capital Mobility in the World: TPP Experience - Kurihara, Yutaka (Archives of Business Research, 2018)
<span style="font-family: 'Times New Roman',serif; font-size: 10pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">TPP without the U.S. has been ongoing. This paper examines the relationship between saving and investment in the Trans-Pacific Partnership<span style="font-family: 'Times New Roman',serif; font-size: 10pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">(TPP) economies. Global saving in the world has been used for investment financing in other regions where domestic and regional finance markets are not well organized. TPP countries, in general, have well organized financial markets of their own, however, better opportunities would be provided for TPP economies if the stronger market integration is accomplished. The empirical results indicate that the role of reginal saving has been important in Asia, however, the U.S. saving-investment has been playing important role for TPP economies.